Risk of Valproic Acid-Related Tremor: A Systematic Review and Meta-Analysis - Zhang, Chen qi; He, Bao ming; Hu, Mei ling; Sun, Hong bin (Frontiers in Neurology, 2020)
Purpose: To evaluate the incidence and risk of tremor in patients treated with valproic aid (VPA) monotherapy. Methods: We searched the PubMed, Embase and Cochrane Library databases to gather relevant data on tremor in patients taking VPA and other drugs and performed a meta-analysis using Stata15.1 software. Results: Twenty-nine randomized controlled trials (RCTs) met the inclusion criteria and were included in the meta-analysis. The overall incidence of tremor in patients receiving VPA therapy was 14% [OR=0.14, 95% CI (0.10-0.17)]. The pooled estimate risk of tremor showed a significant difference between patients treated with VPA and all other drugs [OR=5.40, 95% CI (3.22-9.08)], other antiepileptic drugs (AEDs) [OR=5.78, 95% CI (3.18-10.50)] and other non-AEDs [OR=4.77, 95% CI (1.55-14.72)]. Both a dose of less than 1500 mg/d of VPA [included 500 mg/d: OR=3.57, 95% CI (1.24-10.26), 500-999 mg/d: OR=3.99, 95% CI (1.95-8.20), 1000-1499 mg/d: OR=8.82, 95% CI (3.25-23.94)] and a VPA treatment duration of less than 12 m [included ≤3 months: OR=3.06, 95% CI (1.16-8.09), 3-6 months: OR=16.98, 95% CI (9.14-31.57), and 6-12 months: OR=4.15, 95% CI (2.74-6.29)] led to a higher risk of tremor than did other drugs, as did higher doses and longer treatment times. Conclusion: Compared with other drugs, VPA led to a higher risk of tremor, and the level of risk was associated with the dose and duration of treatment.